2010
DOI: 10.1093/neuonc/nop071
|View full text |Cite
|
Sign up to set email alerts
|

Loss of 1p, 19q, and 10q heterozygosity prospectively predicts prognosis of oligodendroglial tumors—towards individualized tumor treatment?

Abstract: The purpose of this study was to determine whether chromosome 10q loss is a predictor of tumor aggressiveness and poor clinical outcome in patients with oligodendroglial tumors alone or together with loss of heterozygosity (LOH) on chromosomes 1p and 19q. A microsatellite analysis was performed on sections from 130 patients with grade II and grade III oligodendroglial tumors to assess the allelic status of chromosomes 1p, 19q, and 10q, plus detailed clinical and radiological information was taken prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Our study also showed that anaplastic histology is a strong predictor of tumor progression regardless of the degree of resection. Although there are enormous interests on the molecular staging of intracranial ependymoma, currently no specific tumor marker has been validated for a reliable predictor of prognosis and therapeutic response, such as hypermethylation of O 6 -methyl-guanine-DNA methyltransferase in glioblastoma or 1p/19q loss in oligodendroglioma [32,33]. Therefore, anaplastic histology along with mitotic count and Ki-67 index can be used as universal and easily available prognostic parameters in infratentorial ependymoma.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that anaplastic histology is a strong predictor of tumor progression regardless of the degree of resection. Although there are enormous interests on the molecular staging of intracranial ependymoma, currently no specific tumor marker has been validated for a reliable predictor of prognosis and therapeutic response, such as hypermethylation of O 6 -methyl-guanine-DNA methyltransferase in glioblastoma or 1p/19q loss in oligodendroglioma [32,33]. Therefore, anaplastic histology along with mitotic count and Ki-67 index can be used as universal and easily available prognostic parameters in infratentorial ependymoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several tumor suppressors have been identified on 10q, most notably PTEN, which normally serves as a brake on the oncogenic receptor tyrosine kinase pathways (26). Some studies have shown 10q deletion to be an adverse prognostic marker in oligodendrogliomas (7, 27, 28), but not all studies have shown this correlation (9). Recent work in particular has suggested that 10q LOH is more important than 1p/19q status insofar as oligodendrogliomas with codeletion still behave much worse if 10q is also deleted (28).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical characteristics, radiologic features, genetic changes, and extent of resection all play important roles in determining the prognosis of patients with AG. [1][2][3][4][5][6][7][8][9] Interaction and synergy may exist among these factors. The presence of contrast enhancement on MR images, which is based on pathophysiologic changes indicating the destruction of the blood-brain barrier, is considered a specific radiologic feature of high-grade gliomas.…”
mentioning
confidence: 99%